Swollenin pre-conditioning: optimization studies and application aiming at D-lactic acid production from sugarcane bagasse - Modesto, Luiz Felipe (2018)
The enzymatic hydrolysis still stands as a challenge regarding the use of renewable feedstocks, as well as of lignocellulosic materials. The present work reports optimization of swollenin addition to pretreated sugarcane bagasse, in a step prior to the enzymatic hydrolysis, named pre-conditioning. Also, it describes further fermentation of the hydrolyzed material to D-lactic acid. Trichoderma harzianum enzymatic cocktail was produced from pretreated sugarcane bagasse, while swollenin was produced using Aspergillus niger as a host for recombinant protein expression. For pre-conditioning optimization, a Central Composite Rotatable Design was applied and validated. The optimized conditions were used to produce the hydrolysate that was fermented to D-lactic acid by Lactobacillus coryniformis subsp. torquens. It could be observed that pre-conditioning effectively leads to improvements in glucose release: 62% of hydrolysis efficiency. Besides, it was possible to use the produced hydrolysate to obtain D-lactic acid, with a yield of 1.34 g/g and a productivity of 1.59 g/L h-1 .